CR- Submanifolds of a Nearly Trans-Hyperbolic Sasakian Manifold with a Quarter Symmetric Semi Metric Connection - Shamsur Rahman (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2016)
The object of the present paper is to initiate the study contact CR- submanifolds of a nearly trans-hyperbolic Sasakian manifold with a quarter symmetric semi metric connection. For this, some properties of CR- submanifolds of a nearly trans-hyperbolic Sasakian manifold with a quarter symmetric semi metric connection are investigated which conclude that CR- submanifolds of a nearly trans-hyperbolic Sasakian manifold with a quarter symmetric semi metric connection exists with respect to the ?????horizontal and ?????vertical.